The defeated and the dead : teaching about war through film - Pearcy, Mark, 1970- (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"How do we teach about war? How can social studies teachers empower students to understand how wars are started, how they are fought, and how they are ended? Films about war are featured in nearly all social studies classrooms across the US-- Practically every American teenager has seen at least one "historical" film in their time in middle and high school, movies they probably otherwise wouldn't have seen. Film is the medium through which most Americans learn about their national past. But a passive viewing of a movie about war does little to help students learn to be critical thinkers about their country's choices. In The Defeated and the Dead: Teaching about War through Film, Dr. Mark Pearcy outlines strategies and resources for teachers to incorporate movies about war into their classes in an effective, thoughtful manner. Employing elements of the "Just War" doctrine (the basis for most international law and treaties), this book highlights how teachers can make use of widely-used films like Saving Private Ryan, Platoon, and Glory, as well as other movies that span our nation's history, from the American Revolution to modern conflicts. By focusing on critical frameworks like Just War, as well as featuring films both about war and the avoidance of war, The Defeated and the Dead offers social studies teachers a valuable tool to approach difficult, contentious topics in their classrooms"-- Provided by publisher.
Keywords: War films -- Study and teaching (Secondary) -- United States.; War films -- United States -- History and criticism.; Motion pictures in education -- United States.; United States -- History, Military -- Study and teaching (Secondary) -- Audio-visual aids.; History -- Wars & Conflicts -- General.; Teaching of a specific subject.; Military history.; elektronické knihy; electronic books